Theories Of the Stylistics of The Composite Sentences - Eshchonov Sanjar Erkinbayevich (Genius Journals, 2021)
The aim of the given article is to discuss the problem of stylistic devise, repetition, in composite sentences, to give outline of this very important and frequently used stylistic device, its peculiarities and classification and identify those new classes which were revealed after thoroughly studying the material under investigation.
Keywords: Composite sentences; anadiplosis; repetition; scattered repetition